PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA - Made Bayu Indra Nugraha; Ida Bagus Ketut Surya (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Udayana, 2016)
Telkom company run into problems on the satisfaction of employees ranging from incentives the less, the workplace is less comfortable to issue employee promotions. The research objective was to determine the effect of compensation, work environment and promotion on job satisfaction. The research was conducted at PT. Telkom Indonesia South Bali area. The object of research is compensation, work environment, promotion and employee satisfaction. The samples used as many as 74 people, with a sample random sampling method. Data collected through questioner and observation. The analysis technique used is multiple linear regressions. Based on the analysis concluded that compensation, work environment and promotion of office have a significantly influence job satisfaction.